Antibacterial Activity of Pineapple Peel (Ananas comosus) Eco-enzyme Against Acne Bacterias (Staphylococcus aureus and Prapionibacterium acnes) - Ramadani, Aisyah Hadi; Karima, Rizkya; Ningrum, Riska Surya (Indonesian Journal of Chemical Research, 2022)
Acne (acne vulgaris) is a skin disease caused by infection or inflammation of the pilosebaceous unit. Staphylococcus aureus and Prapionibacterium acnes was the main actor in the infection. Eco-enzyme that is made from pineapple peel has been stated that have inhibitory activity against gram-positive and negative bacteria, also applied as home industry soap. This study objective as scientific support that Eco-enzyme phytochemical compounds had the antibacterial activity to the acne bacteria. Eco-enzyme was composed of pineapple peel, brown sugar, and water with the ratio of 3:1:10 for 3 months fermentation time. Eco-enzyme was screened of its phytochemical compound and antibacterial activity against S.aureus and P.acnes by dilution with various concentrations (1.5625%, 3, 125%, 6.25%, 12.5%, 25%, and 50% v/v) and various control. The minimum inhibition concentration (MIC) was then tested by diffusion method to determine the inhibition zone with 3 replication using the higher concentration (50%, 75%, 100% v/v). The result showed that eco-enzyme has a clear yellow colour, contains tannin and saponin, MIC of S.aureus and P.acnes bacteria is 50%. The dilution test of eco-enzyme gives the most effective concentration to inhibit S.aureus at eco-enzyme 100% (v/v), contrasted to P. acnes which didn’t show the best inhibition concentration.